Bryophytes from coastal ecotone of Raigad, Maharashtra: A checklist - Wangikar H. V.; Shete R.S.; Telave A.B.; Chavan S. J. (The Bioscan, 2024)
In recent years, bryophytes have been studied primarily throughout the Western Ghats, despite less attention made to the coastal area. This study focused on bryophytes in the coastal ecotone. Raigad district situated to northern coastal line of western ghats in Maharashtra. The checklist documents a total of 24 bryophyte taxa recorded in costal ecotone of Raigad. Six liverworts, one hornwort, and seventeen mosses were found. Some of the genera of mosses like Fissidens, Campylopus, and Bryum are found to have largest number of species. In liverworts Riccia and Cyathodium are recorded to be species rich genera and Anthoceros is only representer of hornworts in the coastal ecotone area of Raigad district, Maharashtra.